Dataset on nurses' knowledge, attitude and practice in pressure injury prevention at Sabah, Malaysia - Deena Clare Thomas; Rose A Nain (Elsevier Inc., 2023)
Pressure injuries are a significant problem in healthcare, and understanding the knowledge and practices of nurses in this area is critical to improving patient outcomes. This article presents dataset concerning a survey conducted to assess the knowledge, attitudes, and practices of pressure injury prevention and care among nurses in public hospitals in the West Coast division of Sabah, Malaysia. The study involved 448 nurses who completed a structured questionnaire between April and December 2021, using the Malay version of the Pieper-Zulkowski-Pressure Ulcer Knowledge Test (PZ-PUKT) 2016 questionnaire. The questionnaire included socio-demographic information and three outcome measures related to pressure injury prevention. Quantitative descriptive statistical analysis was used to analyze the survey results. The data suggest that this survey provides insights into nurses' knowledge, attitudes, and practices regarding pressure injury prevention and could inform the development of interventions to improve the prevention and management of pressure injuries in public hospitals.